Social Adaptation of Foreign Students in Regional Universities (Case Study of the Penza Region) - Yuliya A. Lutova; Ekaterina V. Shchanina (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Internationalization is a key aspect of education export and one of the most promising lines of higher education development. For successfully becoming a member of the host community, a foreign student as an object of research is forced to assimilate and accept new cultural patterns. However, even when entering a new socio-cultural environment under the most favorable conditions, adaptation difficulties and problems usually arise. The purpose of the article is to identify the factors and conditions for the successful adaptation of foreign students in regional universities using the example of the Penza Region’s universities. The research is based on scientific concepts of students’ social adaptation in a university, as well as concepts of an educational environment creation and functioning. The study considers the reasons for choosing Russia as a country of study based on the author’s questionnaire of Penza universities’ foreign students, secondary analysis of sociological research data on similar topics, and analysis of statistical data. The authors discover that foreign students in Russia face difficulties at various levels: linguistic, conceptual, moral, informational, climatic, communicative, pertaining to everyday life, etc. Favorable conditions contribute to increasing the university’s prestige and the education internationalization levels, become an important factor for choosing an educational institution and quickly including foreign students in the educational process.